Ação do trimetafosfato de sódio sobre a hidroxiapatita durante ciclagem de pH: análise bioquímica, por espectrometria de infravermelho e difração de raios-x - Souza, José Antonio Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Studies have shown that sodium trimetaphosphate (TMP) has a preventive effect in dental enamel demineralization when associated with low fluoride (F) concentrations, but the mechanisms by which TMP acts in enamel is still uncertain. The aim of this study was to analyze the effect of TMP and/or F in hydroxyapatite (HA). HA was prepared by precipitation (calcium nitrate and ammonium phosphate) and matured during 7 days (37 ºC). The precipitate was separated by filtration, dried (70 ºC) and ground to obtain particles between 75 and 53 μm in diameter. Synthetic HA (n=5) was suspended in TMP solutions (100 mL) and divided into the following groups: placebo (deionizer water), 500 (500 μg F/mL), 1,100 (1,100 μg F/mL), TMP 1%, TMP 3%, 500 TMP 1% and 500 TMP 3%. The pH-cycling regimen was repeated 3 times, by lowering the solution's pH to 4.0 and, after 30 minutes, rising to pH 7.0 (37 ºC). After 24 of maturation, the precipitate was dried at 70 ºC for 24 hours, ground into a fine powder (53 μm in diameter) and characterized by Fourier Transformed Infrared Spectroscopy (FTIR) and X-ray Diffraction (DRX), as well as F, calcium (Ca) and phosphorous (P) analyses. Data was submitted to ANOVA, followed by Bonferroni's test (p<0,05). Results of DRX showed more defined peaks for the group 1,100, when compared to the others. The association of F (500 μg F/mL) with TMP at 1 or 3% resulted in more defined peaks when compared to HA prepared (HAp), TMP 1% and TMP 3%. FTIR analysis showed phosphate bands with higher intensity for the fluoridated groups when compared with the placebo. Peaks were less pronounced in the groups 1,100 and 500 TMP 1%. The association of TMP 1% or 3% to 500 μg F/mL solution increased CaF2 formation 4 and 2-fold, respectively when compared to groups 500 and 1,100 (p<0,05). Groups 1,100, 500 TMP 1% and 500 TMP 3% presented Ca/P molar ratios closer to pure HA. It was concluded that...

Estudos mostram que o trimetafosfato de sódio (TMP) tem ação preventiva na desmineralização do esmalte dentário quando associado a baixas concentrações de fluoreto (F), porém o mecanismo pelo qual o TMP age no esmalte ainda é incerto. O objetivo deste trabalho foi analisar a ação do TMP e/ou F sobre a hidroxiapatita (HA). A HA foi preparada pelo método de precipitação (nitrato de cálcio e fosfato de amônio) e maturada durante 7 dias (37 °C). O precipitado foi separado por filtração, seco (70 °C) e triturado até obter grãos entre 75 e 53 μm de diâmetro. Amostras de HA (n=5) foram suspensas em soluções (100 mL) que definiram os seguintes grupos: placebo (água deionizada), 500 (500 μg F/mL), 1100 (1100 μg F/mL), TMP 1%, TMP 3%, 500 TMP 1% e 500 TMP 3%. A ciclagem de pH foi realizada 3 vezes reduzindo o pH das soluções até 4,0 e, após 30 minutos, elevando para 7,0. Após 24 horas de maturação, o precipitado foi seco a 70 °C por 24 horas, triturado em um pó fino (53 μm) e caracterizado por Espectrometria de Infravermelho (FTIR) e Difração de Raios-X (DRX), assim como análise de F, Cálcio (Ca) e Fósforo (P) sendo os dados submetidos à Análise de Variância, seguida pelo teste de Bonferroni (p<0,05). A DRX mostrou picos mais definidos no grupo 1100 quando comparado aos demais. A associação F (500 μg F/mL) ao TMP 1% ou 3% produziu picos mais definidos quando comparado a HA preparada (HAp), TMP 1% e TMP 3%. O FTIR mostrou que a intensidade das bandas de fosfatos foi maior nos grupos fluoretados em relação ao placebo. Menor intensidade das bandas de carbonato foi observada nos grupos 1100 e 500 TMP 1%. A associação TMP 1% ou 3% à solução de 500 aumentou quatro vezes a formação de CaF2 quando comparada ao grupo 500 e duas vezes em relação ao 1100 (p<0,05). Os grupos 1100, 500 TMP 1% e 500 TMP...
Keywords: Durapatita; Desmineralização do dente; Fluoretos; Durapatite